The use of text messaging to improve attendance in primary care: a randomized controlled trial - Leong, K.C.; Chen, W.S.; Leong, K.W.; Mastura, I.; Mimi, O.; Sheikh, M.A.; Zailinawati, A.H.; Ng, C.J.; Phua, K.L.; Teng, C.L. (Oxford University Press, 2006)
Background. Non-attendance is common in primary care and previous studies have reported that reminders were useful in reducing broken appointments. Objective. To determine the effectiveness of a text messaging reminder in improving attendance in primary care. Design. Multicentre three-arm randomized controlled trial. Setting. Seven primary care clinics in Malaysia. Participants. Patients (or their caregivers) who required follow-up at the clinics between 48 hours and 3 months from the recruitment date. Interventions. Two intervention arms consisted of text messaging and mobile phone reminders 24-48 hours prior to scheduled appointments. Control group did not receive any intervention. Outcome measures. Attendance rates and costs of interventions. Results. A total of 993 participants were eligible for analysis. Attendance rates of control, text messaging and mobile phone reminder groups were 48.1, 59.0 and 59.6, respectively. The attendance rate of the text messaging reminder group was significantly higher compared with that of the control group (odds ratio 1.59, 95 confidence interval 1.17 to 2.17, P = 0.005). There was no statistically significant difference in attendance rates between text messaging and mobile phone reminder groups. The cost of text messaging reminder (RM 0.45 per attendance) was lower than mobile phone reminder (RM 0.82 per attendance). Conclusions. Text messaging reminder system was effective in improving attendance rate in primary care. It was more cost-effective compared with the mobile phone reminder.